Synthesis of Some Complexes of Antimony(III) with Polyhydric Phenols, Acid Amides and Indene - Dabas, P.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Reactions of antimony trichloride with polyhydric phenols (catechol, resorcinol, quinol, pyrogallol and phloroglucinol) in presence of amides (formamide, dimethylformamide and urea) leads to the formation of complexes of the type Sb(OnPh)2(A)2Cl. On treatment of these complexes with sodium indenide in THF yields indenyl derivatives of the type Sb(OnPh)2(A)2In. These compounds on slow heating lose the amide molecule to give complexes of the type Sb(OnPh)2In. The complexes have been characterized by elemental analysis, IR and electronic spectra, molecular weight determination, conductivity measurements and magnetic susceptibility measurements. It is suggested that the indenyl ring is σ-bonded to the antimony in the first two types of complexes but there appears to be a transition between the σ-bonded and π-bonded character of the indenyl ring in the third type. The amide molecules enter into the coordination sphere of antimony and the polyhydric phenols behave as monoacid ligands. (Ph is the phenolic residue, n is 2 or 3, In is the indenyl group and THF is tetrahydrofuran.) .